Des frontières à l’origine d’identités montagnardes éclatées. L’exemple des anciens États de Piémont‑Savoie - Alexandre Ruelle (Les Cahiers de Framespa)
At the height of the western Alps, the House of Savoy federate during modern times a multifarious territory – Savoy, Nice, Piedmont and Valle d’Aosta – in which are juxtaposed and expressed by Highlander identities ruptured because of the distinctives linguistic, cultural and politics. These internals fragmentations make it a “border state” which, on a continental scale, takes the form of a “border state” squeezed between two powerful neighbours vying for hegemony: France and the Habsburgs, masters of Milan. Embodied in the concept of Piedmont‑Savoy, this dual dimension of the border means that the Alpine region can be seen as a rich laboratory for political experimentation, conducive to the study of various border effects – wars, boundary conferences and mental representations of old boundaries – conditioned by regional dynamics and the vagaries of European geopolitics.